Assessment of larval settlement under acidification conditions in the gorgonian coral pterogorgia guadalupensis (cnidaria: octocorallia) (2017)
"The study of the development and settlement of coral larvae under low pH conditions is important for understanding how corals and coral reefs will respond to ocean acidification. Here we examine larval development and settlement under acidified conditions in the gorgonian coral Pterogorgia guadalupensis (Duchassaing & Michelin 1846). Brooding events in this octocoral are described as well as subsequent larval stages until colony formation. We found reproductive events in this octocoral to be consistent with yearly bimodal distributions, possibly cued by the new moon. Coral larvae settlement was assessed under six pH conditions on coralline red algae (Hydrolithon boergesenii), and dead gorgonian axis." -- Tomado del Formato de Documento de Grado.